A Personal Journey into the World of Mathematics. Issue 4 (1st April 2020) - Birkar, Caucher; D'Agostino, Susan
Abstract : Caucher Birkar received the 2018 Fields medal for his work in algebraic geometry. This article is based on a talk given by Birkar during the 7th Heidelberg Laureate Forum in Heidelberg, Germany. Birkar chose his current name after he immigrated to the United Kingdom from Iran. The person who introduced this talk noted, "Caucher Birkar means 'migrant mathematician.' In that sense, I am also Caucher Birkar, as are many people in this room."